Unilateral retinoblastoma with contralateral isolated choroidal Melanocytosis: case report of an unexpected presentation - Cassanda C. Brooks; James J. Augsburger; Zélia M. Correa (BMC Ophthalmology, 2018)
Abstract Background Congenital ocular melanocytosis has been shown to be extremely uncommon in studies of numerous infants and children with retinoblastoma and disorders such as retinopathy of prematurity. Case presentation A 33-month-old Caucasian boy presented with a solid white predominantly endophytic retinoblastoma filling most of the nasal aspect of the fundus and extensive vitreous seeding. Fundus exam of the contralateral eye showed a broad-based flat melanotic area of the choroid extending from the subfoveal region to the ora serrata temporally. The child was treated by enucleation of the retinoblastoma-containing eye (homozygous non-germline RB1 mutation) and is being monitored annually. The patient has been followed for 4 years. Conclusions This rare presentation of advanced unilateral retinoblastoma and contralateral isolated choroidal melanocytosis in a young child emphasizes the importance of detailed fundus mapping of the non-affected eye and has potential implications due to the increased incidence of uveal melanoma later in life.